Analysis Of Factors Affecting Milk Productivity Of Dairy Cows In Boyolali District - Nur Khayati, Nur Khayati; Dewi Lestari, Retna; Sepfrian, Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze the factors affecting cow's milk productivity in Boyolali District, which is known as the largest milk producer in Central Java. Despite high production levels, milk productivity per cow in this area is still low, reaching an average of 6 liters per day. Factors analyzed include cow breed, forage feed cost, concentrate feed cost, and frequency of vitamin administration. The analytical method used was multiple linear regression. The results showed that forage feed cost and concentrate feed cost had a significant influence on milk productivity with a significance value, namely the cost of forage feed is 0.003 smaller than 0.005 and the cost of concentrate feed has a significance value of 0.007 smaller than 0.05and milk productivity was influenced by 21% by the variables studied, while 79% was influenced by other factors not explained in this study. This study is expected to provide insight for farmers and other stakeholders to improve milk productivity through better feed management and utilization of more economical feed alternatives.